USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE LESSON (Conference Zone, 2022)
In the field of education, pedagogy and information - communicationtechnologies, internet information educational resources and conferenceThe use of the method allows students to share their knowledge at a high level.effectively help them to become qualified professionals in the futurecreates an opportunity.